Paramolar tubercle-Bolk cusp: A case report - Shivani Sharma; Sumit Tyagi; Vimal Kumar (Wolters Kluwer Medknow Publications, 2018)
Human teeth may show variations which may be found on the crown, either in the form of anomalous cusps or in an increased number of roots which, in some instances, are associated with an anomalous cusp. This paper describes the incidental finding of an uncommon dental trait like "Bolk cusp" or "tuberculum paramolare" or "paramolar tubercle." Paramolar tubercle is an additional cusp occurring on the buccal surface of a permanent maxillary molar. The presence of these extra cusps may be associated with dental problems such as caries, sensitivity, occlusal interference, and hence, there is a need for continuous dental surveillance.